Characterization of Mycobacterium salfingeri sp. nov.: A novel nontuberculous mycobacteria isolated from a human wound infection - Musser, Emily; Smith, Carol; Halse, Tanya A.; Kohlerschmidt, Donna; Rourke, Amy; Fiero, Alexandra; Musser, Kimberlee A.; Escuyer, Vincent; Lapierre, Pascal (Frontiers in Microbiology, 2022)
Nontuberculous mycobacteria (NTM) are environmental bacteria commonly found in soil and water in almost every part of the world. While usually non-pathogenic, they can cause acute respiratory and cutaneous infections under certain circumstances or in patients with underlying medical conditions. Contrary to members of the Mycobacterium tuberculosis complex, documented human-to-human transmissions of NTM have been rarely reported and most cases result from direct environmental exposure. Here we describe the identification of a new NTM species isolated from a hand laceration of a New York State patient after a fall. This new NTM forms rough, orange pigmented colonies and is naturally resistant to doxycycline and tobramycin. Whole genome analysis reveal no close relatives present in public databases, and our findings are in accordance with the recognition of a new taxonomic species of NTM. We propose the name Mycobacterium salfingeri sp. nov. for this new NTM representative. The type strain is 20-157661T (DSM = 113368T, BCCM = ITM 501207T).